Ornamentalism - Cheng, Anne Anlin (New York Oxford University Press, 2019)
Focusing on the cultural and philosophic conflation between the 'oriental' and the 'ornamental', Ornamentalism offers an original and sustained theory about Asiatic femininity in western culture.

This study pushes our vocabulary about the woman of color past the usual platitudes about objectification and past the critique of Orientalism in order to formulate a fresher and sharper understanding of the representation, circulation, and ontology of Asiatic femininity.

This book alters the foundational terms of racialized femininity by allowing us to conceptualize race and gender without being solely beholden to flesh or skin. Tracing a direct link between the making of Asiatic femininity and a technological history of synthetic personhood in the West from the nineteenth to the twenty-first century, Ornamentalism demonstrates how the construction of modern personhood in the multiple realms of law, culture, and art has been surprisingly indebted to this very marginal figure and places Asian femininity at the center of an entire epistemology of race. Drawing from and speaking to the multiple fields of feminism, critical race theory, visual culture, performance studies, legal studies, Modernism, Orientalism, Object Studies and New Materialism, Ornamentalism will leave reader with a greater understanding of what it is to exist as a 'person-thing' within the contradictions of American culture.
Keywords: Feminine beauty (Aesthetics) -- Social aspects; Orientalism in motion pictures; Orientalism -- History; Femininity -- Social aspects; Women -- Asia -- Public opinion